Effect of Andaliman (Zanthoxylum acanthopodium DC) Supplementation in Broiler Diets on Meat Fat, Cholesterol, and Malondialdehyde Content - Anwar, Pajri; Indrawanis, Elfi; Jiyanto, Jiyanto; Santi, Melia Afnida (Faculty of Agriculture, 2024)
This study aimed to evaluate the impact of supplementing broiler diets with andaliman (Zanthoxylum acanthopodium DC) on the fat, cholesterol, and malondialdehyde (MDA) content in broiler meat. The experiment utilized 200 day-old chicks (DOC) of the CP 707 strain, which were fed experimental diets starting at 15 days of age. The average initial body weight was 4651.50 g per bird, and the birds were reared until 35 days of age. The research design followed a Completely Randomized Design (CRD) with five dietary treatments and four replications per treatment, each containing 10 broilers. The dietary treatments included a basal diet (R1= 0% andaliman) and diets supplemented with 0.25% (R2), 0.5% (R3), 0.75% (R4), and 1% (R5) andaliman. The variables measured were meat fat content, cholesterol content, and MDA levels. The results indicated that andaliman supplementation had no significant effect (P0.05) on the fat, cholesterol, or MDA content of broiler meat. The observed ranges were 140.61161.61 mg/100 g for fat content, 140.61161.61 mg/100 g for cholesterol content, and 8.118.56 g/g for MDA levels. In conclusion, the addition of andaliman to broiler diets did not significantly influence the fat, cholesterol, or MDA content in the meat.